2017
DOI: 10.1002/ppul.23927
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response relationship between weight status and clinical outcomes in pediatric influenza‐related respiratory infections

Abstract: These findings demonstrated that underweight status is a risk factor for repeated hospital admissions because of influenza-related respiratory infections in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Finally, even though the previous studies showed positive associations between urinary BPA and obesity among both children and adults using the NHANES database, several cohort and cross‐sectional studies in the United States and other countries did not support these findings . Further cumulative reliable evidence based on prospective cohort studies are needed to confirm whether the association between BPA and obesity is causal or spurious associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, even though the previous studies showed positive associations between urinary BPA and obesity among both children and adults using the NHANES database, several cohort and cross‐sectional studies in the United States and other countries did not support these findings . Further cumulative reliable evidence based on prospective cohort studies are needed to confirm whether the association between BPA and obesity is causal or spurious associations.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of childhood obesity increased between the period from 1990 to 2007 and then leveled off . Recently, several studies have reported that paediatric obesity was associated with high illness severity for acute and chronic diseases, and the health care costs attributable to obesity were gradually rising …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a total of 7 studies were included in the quantitative analysis [45][46][47][48][49][50][51]. Five more studies [52][53][54][55][56] were included in the qualitative analysis.…”
Section: Study Selection Study Characteristicsmentioning
confidence: 99%
“…al, found similar findings across multiple diagnoses, including respiratory syncytial virus and influenza. Each lower respiratory tract disease was studied separately, however 7,8 …”
Section: Introductionmentioning
confidence: 99%